Cavity-magnon polaritons strongly coupled to phonons - Rui-Chang Shen; Jie Li; Yi-Ming Sun; Wei-Jiang Wu; Xuan Zuo; Yi-Pu Wang; Shi-Yao Zhu; J. Q. You (Nature Communications)
Abstract Building hybrid quantum systems is a crucial step for realizing multifunctional quantum technologies, quantum information processing, and hybrid quantum networks. A functional hybrid quantum system requires strong coupling among its components, however, couplings between distinct physical systems are typically very weak. Here we demonstrate the realization of triple strong coupling in a polaromechanical hybrid system where polaritons, formed by strongly coupled ferromagnetic magnons and microwave photons, are further strongly coupled to phonons. We observe the corresponding polaromechanical normal-mode splitting. By significantly reducing the polariton decay rate via realizing coherent perfect absorption, we achieve a high polaromechanical cooperativity of 9.4 × 103. A quantum cooperativity much greater than unity is achievable at cryogenic temperatures, which would enable various quantum applications. Our results pave the way towards coherent quantum control of photons, magnons and phonons, and are a crucial step for building functional hybrid quantum systems based on magnons.